Support for patients with celiac disease: A literature review. Issue 2 (April 2015) - Ludvigsson, Jonas F; Card, Tim; Ciclitira, Paul J; Swift, Gillian L; Nasr, Ikram; Sanders, David S; Ciacci, Carolina
Background: Celiac disease (CD) is a lifelong disorder. Patients are at increased risk of complications and comorbidity. Objectives: We conducted a review of the literature on patient support and information in CD and aim to issue recommendations about patient information with regards to CD. Methods: Data source: We searched PubMed for English-language articles published between 1900 and June 2014, containing terms related to costs, economics of CD, or education and CD. Study selection: Papers deemed relevant by any of the participating authors were included in the study. Data synthesis: No quantitative synthesis of data was performed. Instead we formulated a consensus view of the information that should be offered to all patients with CD. Results: There are few randomized clinical trials examining the effect of patient support in CD. Patients and their families receive information from many sources. It is important that health care personnel guide the patient through the plethora of facts and comments on the Internet. An understanding of CD is likely to improve dietary adherence. Patients should be educated about current knowledge about risk factors for CD, as well as the increased risk of complications. Patients should also be advised to avoid other health hazards, such as smoking. Many patients are eager to learn about future non-dietary treatments of CD. This review also comments on novel therapies but it is important to stress that no such treatment is available at present. Conclusion: Based on mostly observational data, we suggest that patient support and information should be an integral part of the management of CD, and is likely to affect the outcome of CD.